Evaluation of Parenchymal Thyroid Diseases Using Ultrasonography - Naveen BS (Asian Journal of Medical Radiological Research, 2020)
Background: Thyroid diseases are among the most common endocrine disorders seen in all age groups. The present study was conducted to determine parenchymal thyroid diseases using Ultrasonography (USG) in adult patients. Subjects and Methods: This study was conducted on 140 adult patients. Patients were divided into five groups such as Group I (normal); Group II had first detected, early untreated Hashimoto disease (EH); Group III comprised of chronic Hashimoto patients that are under treatment and/or follow up (H); Group IV had multinodular parenchymal hyperplasia (M); and Group V had nodular hyperplasia with Hashimoto (HM). They underwent spectral Doppler ultrasound and acoustic radiation force impulse using Siemens ACUSON S2000 machine. Results: The mean RI in group I was 0.54, in group II was 0.56, in group III was 0.42, in group IV was 0.48 and in group V was 0.49, mean AT in group I was 26.2, in group II was 25.3, in group III was 71.3, in group IV was 46.2 and in group V was 45.1, mean SWV in group I was 1.54, in group II was 1.72, in group III was 1.20, in group IV was 1.46 and in group V was 1.65. The difference was significant (P< 0.05). Conclusion: Authors found that resistivity index, acceleration time and shear wave velocity together are reliable for differential diagnosis of parenchymal thyroid diseases.